Factors Affecting Patient Perceptions and Satisfaction with Telemedicine in Outpatient Clinics - SA Abdulwahab (SAGE Publishing, 2021)
Despite the increasing use of telemedicine, patients’ views on telemedicine remain unclear. This study aimed to understand factors affecting patient perceptions and satisfaction with telemedicine services. 235 patients were surveyed on accessibility to telemedicine clinics, medical specialities and satisfaction with the services. 58.3% confirmed having a stable internet connection, 24.3% used telemedicine services in internal medicine clinics, and only 5.1% accessed the telemedicine services in psychiatry clinics. 68.5% used the telephone to access telemedicine service, while only 6.4% used the hotline. Over half of patients confirmed their ability to hear clearly and speak easily with their healthcare providers during their consultations. 55.7% confirmed they were satisfied with their telemedicine experience, while 23.4% were neutral and 8.9% were unsatisfied. There was a significant difference in the rates of satisfaction between female and male respondents (p-value<0.001). Those with stable internet connection had significantly higher satisfaction rates with telemedicine services (p-value<0.001). The rates of satisfaction with telemedicine services were significantly higher in Cardiology and Orthopaedic clinics. Larger multi-center studies examining other factors affecting patients’ satisfaction are recommended.